2017
DOI: 10.1038/oncsis.2017.40
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: α2,6-Sialylation mediates hepatocellular carcinoma growth in vitro and in vivo by targeting the Wnt/β-catenin pathway

Abstract: Abnormal sialylation due to overexpression of sialyltransferases has been associated with tumorigenesis and tumor progression. Although ST6Gal-I influences cancer persistence and progression by affecting various receptors, the underlying mechanisms and mediators remain largely obscure, especially in hepatocellular carcinoma (HCC). We found that ST6Gal-I expression was markedly upregulated in HCC tissues and cells, high levels being associated with aggressive phenotype and poor prognosis. Furthermore, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Moreover, its expression has been associated with changes in adhesion, metastasis and poor prognosis . In our previous work, we demonstrated that ST6Gal‐I may act as a tumor promoter in hepatocarcinoma and prostate cancer cells . In the present study, we demonstrated that silencing of ST6Gal‐I resulted in reduced cell proliferation, clonogenic, migration and invasion ability of A549 and H1299 NSCLC cells in vitro , which could be rescued by the reintroduction of ST6Gal‐I and Notch1.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Moreover, its expression has been associated with changes in adhesion, metastasis and poor prognosis . In our previous work, we demonstrated that ST6Gal‐I may act as a tumor promoter in hepatocarcinoma and prostate cancer cells . In the present study, we demonstrated that silencing of ST6Gal‐I resulted in reduced cell proliferation, clonogenic, migration and invasion ability of A549 and H1299 NSCLC cells in vitro , which could be rescued by the reintroduction of ST6Gal‐I and Notch1.…”
Section: Discussionsupporting
confidence: 59%
“…Effects of ST6Gal‐I on cancer progression is quite controversial, being either inhibitive or facilitative. ST6Gal‐I overexpression has been reported in several types of cancer, including liver, prostate, ovarian and colorectal carcinomas . Our previous study found that ST6Gal‐I improved hepatocarcinoma cells (HCC) proliferation, migration and invasion, and modulated docetaxel sensitivity in HCC via the p38 MAPK/caspase pathway .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a former study has demonstrated that SOX9 can regulate Wnt/β‐catenin pathway to promote stemness in HCC (Leung et al ., ). The Wnt/β‐catenin pathway has been largely reported as crucial signaling in the regulation of progression and metastases in HCC (Chao et al ., ; Hu et al ., ; Zhao et al ., ). Therefore, we wondered whether SOX9 and SOX9‐AS1 could regulate the Wnt/β‐catenin pathway in HCC.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, several studies have reported that SOX9 could regulate the Wnt/β‐catenin pathway in human cancers (Cui et al ., ; Guo et al ., ; Santos et al ., ), including HCC (Leung et al ., ). The Wnt/β‐catenin pathway has been recognized as a key pathway implicated in HCC progression and metastasis (Chao et al ., ; Hu et al ., ; Zhao et al ., ). Herein, we showed that silencing SOX9 or SOX9‐AS1 could attenuate the Wnt/β‐catenin pathway, thereby inhibiting EMT.…”
Section: Discussionmentioning
confidence: 97%